Analysis of Judges' Considerations in Inheritance Rights Disputes with Fictitious Death Claims and the Psychological Competence of the Parties (Study of Decision Number: 457/Pdt.G/2020/PA.Plk) - Ali, Nuraliah; Laksana, Andri Winjaya (Jurnal Hukum Khaira Ummah, 2025)
Decision Number 457/Pdt.G/2020/PA.Plk decided by the Palangka Raya Religious Court presents the complexity of inheritance disputes that include two main issues, namely the claim of fictitious death against one of the heirs and the alleged legal incapacity due to a history of mental disorders. This dispute shows the challenges in assessing the validity of the legal status of the heirs and its implications for the right to inheritance. This study aims to analyze the judge's considerations in resolving the dispute and evaluate its compliance with the principles of justice, legal certainty, and Islamic legal norms. The method used is a normative legal approach with content analysis techniques on primary legal materials in the form of court decisions, the Compilation of Islamic Law (KHI), and the Civil Code (KUHPerdata), as well as relevant secondary and tertiary legal materials. Data collection techniques are carried out through document studies of regulations, academic literature, and court decision documents. The results of the study show that the panel of judges rejected the claim of fictitious death on legal grounds, namely that it was not supported by formal evidence such as a death certificate or court decision, in accordance with the provisions of Article 44 of the Civil Code and Article 171 of the Compilation of Islamic Law. The plaintiff's physical presence at the trial and a valid official identity confirmed his legal status as a living party and entitled to inheritance. The claim regarding mental disorders was declared baseless because there was no determination of guardianship based on Article 433 of the Civil Code, and the 2014 medical history was not relevant to assess the plaintiff's legal condition at the time the dispute took place in 2020. During the trial process, the plaintiff was also considered to have demonstrated behavior that reflected legal competence. In his verdict, the judge decided on the distribution of the inheritance based on the principles of Islamic inheritance law, namely that the sons receive a share of 2/8, the daughters each 1/8, and the remainder is distributed to other heirs according to their lineage. The inheritance was ordered to be auctioned, and the proceeds distributed according to the provisions as a form of implementing the principle of justice and protection of the civil rights of all heirs.In general, the judge's considerations in this decision have reflected the principle of justice in Islam, upholding legal certainty through the application of valid evidence, and being consistent with the values of Islamic law in providing legal protection for inheritance rights and the integrity of the judicial process.